Vaccination during pregnancy: Canadian maternity care providers' opinions and practices. Issue 11 (1st November 2020) - Dubé, Eve; Gagnon, Dominique; Kaminsky, Kyla; Green, Courtney R.; Ouakki, Manale; Bettinger, Julie A.; Brousseau, Nicholas; Castillo, Eliana; Crowcroft, Natasha S.; Driedger, S. Michelle; Greyson, Devon; Fell, Deshayne; et al.
ABSTRACT: A number of countries have implemented vaccination in pregnancy as a strategy to reduce the burden of influenza and pertussis. The aim of this study was to assess the involvement of Canadian maternity care providers in administration of vaccines to their pregnant patients. A cross-sectional web-based survey was sent to family physicians, obstetricians-gynecologists, midwives, pharmacists, and nurses. A multivariable logistic regression model was used to determine variables independently associated with offering vaccination services in pregnancy in providers' practice. A total of 1, 135 participants participated. Overall, 64% (n = 724) of the participants reported offering vaccines in their practice and 56% (n = 632) reported offering vaccines to pregnant patients. The main reasons reported for not offering vaccination services in pregnancy were the belief that vaccination was outside of the scope of practice; logistical issues around access to vaccines; or lack of staff to administer vaccines. In multivariable analysis, the main factors associated with vaccination of pregnant patients in practices where vaccination services were offered were: providers' confidence in counseling pregnant patients about vaccines, seeing fewer than 11 pregnant patients on average each week, and being a nurse or a family physician. Although the majority of participants expressed strong support for vaccination during pregnancy, half were not offering vaccination services in their practice. Many were not equipped to offer vaccines in their practice or felt that it was not their role to do so. To enhance vaccine acceptance and uptake in pregnancy, it will be important to address the logistical barriers identified in this study.